The relationship between phytoestrogen-rich supplements and breast cancer: A multicenter case–control study in Saudi Arabia - Alnefaie, Sahar M.; Alwagdani, Nawaf M.; Althobaiti, Rashed A.; Almansori, Khaled M.; Alalawi, Yousef; Al-Kharashi, Eyad I.; Al-Ameer, Ahmed; Abdel Hadi, Maha (International Journal of Health Sciences, 2024)
Objectives: The prospective effect of phytoestrogen-rich supplements has been explored by many researchers in an attempt to reduce breast cancer (BC) risk worldwide. In Saudi Arabia, some widely used supplements have high phytoestrogen content. Therefore, we aimed to (1) assess the relationship between phytoestrogen supplements (PSs) that are widely used among women of Saudi Arabia and BC and (2) assess the relationship based on the menstrual status. Methods: The study took place during 2020–2022 to assess several PSs using a case–control design that included five centers from different provinces around the country. A questionnaire was answered by the participants that included 381 (46%) cases (diagnosed with BC) and 449 (54%) controls (free of BC). The PS items were assessed individually and on the multivariant analysis model. Results: Of the 12 phytoestrogen-rich supplements, soy milk showed a significant decrease in BC risk. However, Echinacea showed an increased risk of BC among its users. A subgroup analysis based on the menstrual status demonstrated an increased risk of BC among licorice root and green tea users on premenopausal and postmenopausal women, respectively. Conclusion: Soy isoflavones continue to show a significant risk reduction that could be used for a modified approach to reduce the risk of BC. However, Echinacea, licorice root, and green tea have shown to increase the risk of BC.